Sentidos atribuídos à integralidade: entre o que é preconizado e vivido na equipe multidisciplinar - SILVA, Marcos Valério Santos da (Universidade Federal do Pará, 2017)
The aim of this paper is to discuss the practitioners’ view about icomprehensiveness in health. This study is part of a Masters’ degree qualitative dissertation, held in Belém, Pará, in the period from june to august 2015. Most participants attributed the meaning of comprehensiveness in health as “a holistic view of the being,” and were able to see the relationship between comprehensiveness and multidisciplinary approach. There is the need todeepen the knowledge of the principles of SUS even during training, to accomplish more effective health actions.